Maternal mortality following caesarean section in a low-resource setting: a National Malawian Surveillance Study - Shakila Thangaratinam; Louise Afran; Maria Lisa Odland; Luis Gadama; David Lissauer; Fannie Kachale; Chifundo Ndamala; Abi Merriel; Catriona Waitt; Amie Wilson; Hussein H Twabi; Annie Kuyere; et al. (BMJ Global Health)
Background Caesarean section (CS) is the most common major surgery conducted globally, with rates rising. CS also contributes to maternal morbidity and mortality, with increased risks in low-resource settings. We conducted a detailed review of maternal deaths from 2020 to 2022 in Malawi to determine the burden of deaths related to CS, avoidable health system factors, and causes of death associated with this procedure.Methods Data were collected regarding every maternal death occurring across all district and central hospitals in Malawi, alongside facility-level aggregated birth data. Maternal deaths were reviewed by facility-based multidisciplinary teams with subsequent confirmation of cause of death by obstetricians according to international criteria. Logistic regression was applied to estimate the odds of associations of leading causes of death with CS while adjusting for potential confounders.Results Despite a low national CS rate, most deaths occurred following CS (51.8%, 276/533). Women who delivered by CS were five times (OR 5.60, 95% CI 4.74 to 6.67) more likely to die than women who delivered vaginally. The leading causes of death following CS were postpartum haemorrhage (26.0%, 68/277), eclampsia (15.6%, 41/277) and infection (14.1%, 37/277). Deaths from pregnancy-related infection were more often associated with CS (OR 2.03, 95% CI 1.12 to 3.72). Health system factors more frequently associated with deaths following CS than vaginal birth included ‘prolonged abnormal observations without action’ (p=0.006), ‘delay in starting treatment’ (p=0.006) and ‘lack of blood transfusion’ (p=0.03).Conclusions We found a high burden of maternal death following CS in this low-resource setting. Until now, international attention and many clinical trials have been focused on improving the safety of vaginal birth. Our findings highlight the need to ensure the safe and appropriate use of this potentially life-saving intervention to reduce maternal deaths. To avoid the high burden of death following CS we highlight, there is urgent need to develop and trial CS-specific interventions.